Inkonsistensi Norma Konstitusional Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Setiawan, Dika (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research delves into the legal implications of Constitutional Court Decision No. 91/PUU- XVIII/2020, focusing on its impact on the inconsistency of Law Number 11 of 2020 and the resulting legal effects. Employing a juridical normative approach, the study examines legal concepts, principles, and regulations. The findings reveal that the Constitutional Court's conditional declaration of unconstitutionality for Law Number 11 of 2020 stems from discrepancies in its formation concerning clarity of purpose, formulation, and transparency, as stipulated by Law Number 12 of 2011 on the Formation of Legislation. The legal effects of Decision No. 91/PUU-XVIII/2020 on Law Number 11 of 2020 within Indonesia's legal system are significant. During the two-year rectification period, it retains legal status and is recorded in the Official Gazette. If no rectification occurs within two years, Law Number 11 of 2020 becomes permanently unconstitutional, and the prior laws it amended or replaced are reinstated. In conclusion, several recommendations are made: The Constitutional Court should issue clear, unambiguous verdicts for legal certainty. The public and academia should monitor government and legislative activities to uphold constitutional principles. This research sheds light on the legal implications of Constitutional Court Decision No. 91/PUU-XVIII/2020 and provides valuable guidance for Indonesia's legal and legislative stakeholders.